PEMANFAATAN BASIS DATA PADA PERPUSTAKAAN DIGITAL UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Diva Anisyah Putri; Indah Sahima Hsb; Antin Ayunda; Tyo Azharil Fikri; Nurbaiti Nurbaiti (Jurnal Inovasi Penelitian, 2023)
At this time technology, information and communication (Science and Technology) is developing very rapidly, and bringing changes in various sectors including the world of libraries, so that the use of technology is very, very important and people from all walks of life have used it. A digital library is a library that stores data in the form of books, pictures, sound in electronic form and distributes it using electronic rules. This study aims to determine the benefits of the database for the UINSU digital library from various electronic resources such as e-journals, e-books, and so on. The research methodology used in this research is qualitative research by collecting data from various journals as well as interviews conducted with UINSU students. With the holding of a digital library by the State Islamic University of North Sumatra, it will make it easier for students to access both books, journals, scientific work, theses and so on with fun tools, namely electronic devices such as gadgets and computers, and users are no longer physically bound during library service hours where visitors have to visit the library to get information. The results of the research show that the database as a system is used for data management with specific functions and purposes so that its use is experiencing rapid development. The presence of this electronic database has brought significant changes and progress to digital libraries, this is due to the existence of a database in digital libraries, especially the UINSU digital library, so it is able to manage various available electronic resources such as e-journals, e-books, repositories and books. classics are similarly arranged and well classified